Building Essay Outline Through Discourse Illustration: Project-Based Learning in Higher Vocational Education - Gusti Nyoman Ayu Sukerti; Kadek Yogi Susana (RETORIKA: Jurnal Ilmu Bahasa, 2018)
Abstract—Project-based learning is an innovative learning model which emphasizes contextual learning through complex activities. Project-based learning focused on learning the core concepts, involving learners in problem-solving investigations and other meaningful tasks, giving students the opportunity to work autonomously construct their own knowledge and ultimately produce a real product. Project-based learning can be used to achieve a certain competency through a project within a specified period through the steps of planning, execution, reporting, communicating the results and evaluation activities. This research was aimed to analyze the use of discourse illustration in writing essay outlines in order to help students in the stage of constructing ideas. This study focused on the use of discourse illustration in the context of teaching English for vocational students with a framework of project-based learning as a basic model. The goal of this method was to improve students’ engagement in writing and ease the obstacles faced when developing ideas. Participants were 28 third semester students enrolled in a three-year undergraduate program in Informatics Management whose English proficiency was lower intermediate. The outlines produced by students were evaluated and discussed in peer review until the drafts were final. The study revealed that students were able to construct a more coherent and cohesive essay and engaged in the completion of the project in a more positive attitude as they could develop their competence in writing and enhance their collaborative skill to work as a team. Keywords:Constructing outline; discourse illustration; essay writing; project-based learning